THE INFLUENCE OF CREDIT MONITORING AND DEBTOR CHARACTER ON BAD CREDITS AT BANK NAGARI, SUNGAI TAMBANG SUB-BRANCH - Rita Dwi Putri; Lili Wahyuni; Fadil Chaniago (Jurnal Ekonomi, 2023)
One of the risks faced by every bank in running its business is credit risk. Credit risk is the risk that arises as a result of the debtor's failure to fulfill obligations. In general, two factors cause bad credit, namely internal factors and external factors. This research aims to determine Bad Credit which is influenced by Credit Monitoring and Debtor Character. This type of research is quantitative research with an associative (relationship) approach. The population of this research is all bad credit customers in 2018-2022 at Bank Nagari, Sungai Tambang Sub-Branch. The sampling technique used was total sampling. The data used is data on bad credit customers at Bank Nagari, Sungai Tambang Sub-Branch. The data sources in this research were obtained from direct observation, questionnaires and interviews with company employees and customers of Bank Nagari, Sungai Tambang Sub-Branch. Partially, the research results show that Credit Monitoring has no effect on Bad Credit and Debtor Character also has no effect on Bad Credit. Meanwhile, simultaneously, Credit Monitoring and Debtor Character influence Bad Credit. Based on the results of the coefficient of determination test, Bad Credit is influenced by Credit Monitoring and Debtor Character by 8.7%. And the remaining 91.3% is influenced by other variables outside of the variables used in this research.